Research Directions on Students’ Nonverbal Communication in Higher Education - Ichim-Radu, Gabriel (Didactica Danubiensis, 2025)
Objectives: This study explores recent developments in research on nonverbal communication in higher education, with particular attention to its role in students’ professional formation. It examines the importance of decoding nonverbal cues for enhancing classroom interaction and student–faculty engagement. Prior Work: Drawing on interdisciplinary insights from psychology, education, and interpersonal communication, the study engages with foundational models (Ekman, Burgoon, Chelcea), as well as more recent research on the expressive and regulatory functions of nonverbal behavior in university teaching and learning. Key concepts addressed include proxemics, facial expressions, gestures, and paralinguistic cues. Approach: The study takes an interpretive stance and explores the nonverbal aspects of academic communication in line with the requirements of professional formation in higher education. It reviews key contributions from the specialized literature that describe models of nonverbal communication relevant to university contexts. Results: Research highlights several key factors that influence students’ nonverbal behavior during oral presentations, including self-confidence, performance anxiety, and cultural background. The study also identifies the core functions of nonverbal communication such as repetition, substitution, complementation, emphasis, and contradiction, and examines how these functions manifest within instructional settings. Implications: The findings provide a conceptual framework for university educators to develop communication practices that are sensitive to nonverbal language. The study recommends ongoing professional development in nonverbal communication, the integration of nonverbal competence into educational quality assurance, and greater recognition of nonverbal feedback in student assessment. Value: Nonverbal communication plays a foundational role in shaping the educational climate in higher education. This study deepens our understanding of the implicit meanings embedded in academic nonverbal interactions and proposes an explanatory model that outlines dimensions of nonverbal communication with pedagogical significance and practical relevance for fostering students’ communicative competencies.